KARAKTERISTIK BAHASA INDONESIA LOGAT PAPUA DAN RELEVANSINYA SEBAGAI MATERI AJAR MATA KULIAH SOSIOLINGUISTIK DI PROGRAM STUDI PENDIDIKAN BAHASA INDONESIA UNIVERSITAS SEBELAS MARET - Prihapsari, Ira; Setiawan, Budhi; Suryanto, Edy (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
This research is a case study research.. The sampling technique is purposive sampling. Source of data used in the form of events, informants, and documents. Data collection technique used are direction observation, interview, and document. The data validity test used is triangulation of source and triangulation method. Data analysis technique used is flow model. The result of this research is description of: (1) the characteristic Indonesian Papuan dialect are divided into linguistic and nonlinguistic elements. The linguistic elements include; (a) phoneme replacement; (b) diphthong replacement; (c) phoneme removal; (d) the use of intonation. Nonlinguistic elements are speech and paralinguistic events; (2) the factors that influence the emergence of Indonesian Papuan dialect are; (a) administrative unity; (b) a specific sense of community identity; (3) the same of geographical area; (d) historical experience; (3) characteristics of Indonesian Papuan dialect has relevance as materials of sociolinguistic subject at Indonesian Language Education Department of Sebelas Maret University.